The Modeling of Tsunami Wave Run-Up and Vulnerability Zone Analysis In Cipatujah, Tasikmalaya District - Tamara Centong Mandey; Aris Ismanto; Denny Nugroho Sugianto; Purwanto Purwanto; Rikha Widiaratih; Gentio Harsono (University of Diponegoro, 2021)
Cipatujah is a sub-district in Tasikmalaya Regency, West Java Province, Indonesia, which is one of the areas affected by significant damage due to tectonic activity in the southern region of Java, namely an earthquake with a magnitude of 7.7 magnitude and West Java tsunami in 2006 after Nusa Kambangan and PangandaranThe purpose of this study is to estimate the tsunami travel time, wave heights distribution, coverage areas, and vulnerability zone based on the Java 17 July 2006 earthquake scenario in Cipatujah, Tasikmalaya Regency. The method used in this study is quantitative and requires bathymetry data, high points, earthquake parameters of July 17, 2006, tidal data, RBI maps, and land use data. Tsunami modeling with numerical simulations using COMCOT v 1.7 and MATLAB software, also Arc Map for mapping tsunami coverage and vulnerability zone areas. Based on data processing, it was found that the maximum wave speed of 3.92 m/s. In the 27th minute, the waves had reached the Cipatujah region, with a maximum run-up height of 6.115 meters and a maximum tsunami range on the land of 1.891 meters. The area affected by the tsunami based on the processing of tsunami coverage data in Cipatujah totals 11.64 km2. Whereas for tsunami vulnerability zone in Cipatujah, it is divided into 3 categories, namely low hazard zone, medium hazard zone, and high hazard zone. This indicates that the Cipatujah region is included in a high tsunami-prone zone. Based on the results of verification and validation with an RSR value of 0,073, then it is assumed that the height of the run-up model is sufficient by the run-up data that occurred during the event.